Theory of Constraints & Consumer Behavior: A Comparative Analysis Between Developed & Advanced Developing Cultures - Powless, Seth; Montoya Jarquin, Nathaly (Journal of Applied Business and Economics, 2023)
This paper investigates a shift in consumer buying behavior because of the recent global pandemic in developing and developed consumer cultures by integrating Goldratt’s Theory of Constraints (TOC) into buying cultures. TOC is the central theoretical framework behind this global catastrophe of product and labor shortages, hyperinflation, and transportation bottlenecks. This research attempts to connect TOC to paradigm shifts in consumer buying culture along with identifying possible solutions to this global phenomenon. The methodology we used to gather data includes a chain-referral sampling model distributed through social media. Findings conclude that emerging countries adjust more swiftly to constraints and had a lesser proclivity to modify purchasing habits because of a pandemic than developed economies, whose consumers suffer economic distress less frequently.